Antimicrobial effects of helix D-derived peptides of human antithrombin III - Papareddy, Praveen (2014)
Antithrombin III (ATIII) is a key antiproteinase involved in blood coagulation. Previous investigations have shown that ATIII is degraded by Staphylococcus aureus V8 protease, leading to release of heparin binding fragments derived from its D helix. As heparin binding and antimicrobial activity of peptides frequently overlap, we here set out to explore possible antibacterial effects of intact and degraded ATIII. In contrast to intact ATIII, the results showed that extensive degradation of the molecule yielded fragments with antimicrobial activity. Correspondingly, the heparin-binding, helix D-derived, peptide FFFAKLNCRL-YRKANKSSKLV (FFF21) of human ATIII, was found to be antimicrobial against particularly the Gram-negative bacteria Escherichia coli and Pseudomonas aeruginosa. Fluorescence microscopy and electron microscopy studies demonstrated that FFF21 binds to, and permeabilizes, bacterial membranes. Analogously, FFF21 was found to induce membrane leakage of model anionic liposomes. In vivo, FFF21 significantly reduced P. aeruginosa infection in mice. Additionally, FFF21 displayed anti-endotoxic effects in vitro. Taken together, our results suggest novel roles for ATIII-derived peptide fragments in host defense.